UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL PADA BUAH BIT (Beta vulgaris L.) MENGGUNAKAN METODE DPPH (2,2-DIPHENYL-1-PICRYLHYDRAZIL) - Dian Sry Rejeki Nadeak; Astriani Natalia br ginting; Daimah Wirdatus Sanaun Harahap (Jurnal Buana Farma, 2026)
Oxidative stress due to the accumulation of free radicals plays a role in the development of various degenerative diseases, so that natural antioxidant sources that can be scientifically evaluated are needed. Beetroot (Beta vulgaris L.) is known to contain bioactive compounds such as betalains, flavonoids, and polyphenols that have the potential as antioxidants. This study aims to evaluate the antioxidant activity of beetroot (Beta vulgaris L.) ethanol extract in vitro using the DPPH method. Extraction was carried out by maceration method using 96% ethanol. The antioxidant activity test was carried out using DPPH solution with absorbance measurement at a wavelength of 517 nm. The extract was tested at a concentration range of 10–100 µg/mL with three replications, while quercetin was used as a positive control. Antioxidant activity was expressed as the percentage of DPPH radical inhibition and the IC₅₀ value calculated using linear regression analysis. The results showed that the beetroot ethanol extract had an IC₅₀ value of 3.35 µg/mL, while quercetin had an IC₅₀ value of 2.76 µg/mL. The yield of the extract obtained was 20.29%. These results indicate that the beetroot ethanol extract has DPPH radical scavenging activity in the in vitro test system used.